Project Bauhaus: Can Design Change Society? - (:unkn) unknown (Birkhäuser, 2019)
We are interested in the Bauhaus from a contemporary perspective - not the fetishization and mythologization of a legacy. In our view, many of the objectives of classical modernism show promise for the present day - be it design's alignment to utility and function, the belief in the emancipatory potential of design, the integration of design with diverse forms of modernday under standing and technologies, or the critique of the present through design. Our focus lies less on actual Bauhaus products than on the school's ambitions and methods. In the interests of a reflective modernism, we want to examine and critically reflect on the history of the development and impact of the historic Bauhaus, so that we can also learn from its mistakes and impasses. This international edition on the work of project bauhaus now offers English readers a comprehensive overview of our multi-year research, artistic, performance, and publication project, which involved the participation of more than a hundred renowned scientists, artists, architects, and designers from around the world.
Keywords: Bauhaus; Baustil; Architekturgeschichte; Designgeschichte; Moderne; Wirkungsforschung; Gesellschaftlicher Wandel; Städtebau; Öffentlicher Raum